2011
DOI: 10.1186/1471-2164-12-597
|View full text |Cite
|
Sign up to set email alerts
|

High resolution profiling of human exon methylation by liquid hybridization capture-based bisulfite sequencing

Abstract: BackgroundDNA methylation plays important roles in gene regulation during both normal developmental and disease states. In the past decade, a number of methods have been developed and applied to characterize the genome-wide distribution of DNA methylation. Most of these methods endeavored to screen whole genome and turned to be enormously costly and time consuming for studies of the complex mammalian genome. Thus, they are not practical for researchers to study multiple clinical samples in biomarker research.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…A LHC-BS approach [14,15] was subsequently applied to profile the promoter methylome of the 8 sample pairs. Promoters were denoted as regions from −2200 bp to +500 bp of the transcriptional start sites (TSS) [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A LHC-BS approach [14,15] was subsequently applied to profile the promoter methylome of the 8 sample pairs. Promoters were denoted as regions from −2200 bp to +500 bp of the transcriptional start sites (TSS) [16].…”
Section: Resultsmentioning
confidence: 99%
“…Although this has been extensively studied in colon cancer, with many genes identified as harboring altered methylation in their promoter CGIs [21], there is currently far less information regarding HCC. Our previous study showed that the novel LHC-BS approach is a reliable and efficient analytical platform for generating a single-base-pair resolution methylome map of promoter regions in cancer and normal cell lines [14,15]. In the current study, we further optimized the technology to profile the promoter methylome in 8 paired HCC samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We term these approaches as bisulfite oligonucleotide capture sequencing (BOCS). Several very similar approaches have been developed for assessing the human (Wang et al 2011;Ivanov et al 2013;Allum et al 2015;Li et al 2015), mouse (Hing et al 2015;Li et al 2015), and rat (Masser et al 2016) genomes. In all of these approaches, capture of targeted regions is by complimentary oligonucleotide probes.…”
Section: Oligonucleotide Capturementioning
confidence: 99%
“…Moreover, as an alternative to WGBS, other next generation sequencing methods have been developed in mammalian genomes for the analysis of medium to high number (100-140,000) of candidate regions as cost, genome complexity and DNA quantities can be an obstacle to the use of WGBS (Lee et al 2013). These methods are based on the capture of targeted regions of interest to enrich target sequences prior to or after bisulfite conversion using bisulfite padlock probes (Ball et al 2009), solution hybrid selection (Wang et al 2011), array capture (Hodges et al 2009) or microdroplet PCR (Komori et al 2011), but often require a significant amount of input DNA. Further, PCR amplification products of bisulfite treated DNA can also be sequenced on next generation sequencing instruments (Nones et al 2014), and which might circumvent some of the inherent limitations of pyrosequencing such as quantification in hompolymers.…”
Section: Measurement Of the Efficiency Of Sodium Bisulfite Conversionmentioning
confidence: 99%